Development of Socially Active Citizenship Competences in Educating Primary School Students' Spiritual Thinking - Abdullayeva Shohista Maksudovna; N. H. Aslanova (Researchparks Publishing, 2023)
The article describes the development of competence of primary school students, the types of competence. For this purpose, important factors in the formation of scientific competences (communicative competence, information processing competence, self–development competence) are shown, and the Uzbek people have their mental image, national character, character, feeling , customer, behavior, morals, taste, tastes are different, the improvement of the child's morals and manners should be done first of all in the family.